If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12z + -9 = 39 Reorder the terms: -9 + 12z = 39 Solving -9 + 12z = 39 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 12z = 39 + 9 Combine like terms: -9 + 9 = 0 0 + 12z = 39 + 9 12z = 39 + 9 Combine like terms: 39 + 9 = 48 12z = 48 Divide each side by '12'. z = 4 Simplifying z = 4
| 8y+15=119 | | 6y+18=90 | | 2x^2-9x+6=0 | | Sn=8n-2n^2 | | -14b+10-6b=20b+30-15+40 | | 4x-4=18+x | | 9k-7+8=-6k+44 | | 5+5x=-10x | | -10y+9+3y=5y-27 | | x+(2x+9)-6=5x-(3+2) | | 8=2t+1 | | c=2t+1 | | 5+5x=-10x+80 | | 2x+10+4x-1=180 | | 2w+w+2w+w=30 | | x+3+x-4x=51 | | 2w+w+2w+w= | | 9x-4=18+x | | 3k^2+k=6 | | 3z^4+20z^3+6z^2-20z=-3 | | 0.14y=28 | | 0.04x=1.6 | | 2x+3+115=0 | | 0.3y=9 | | 23544x=90 | | 0.1x=2 | | X=2+2x-4 | | 2343x=90 | | y+2.5=10 | | X=9+9(x-9) | | 324x=90 | | x-1.3=1 |